Antioxidative constituents of Mitragyna diversifolia plant extract and their protective effect on H2O2-induced oxidative stress in L6 myotubes - Ilham Hama, Phanita Vonghirundecha, Boonsong Wungsintaweekul, Rinnapat Boonsut, Supattra Limsuwanchote, Juraithip Wungsintaweekul (Journal of Applied Pharmaceutical Science, 2025)
This study aimed to evaluate the antioxidative constituents of Mitragyna diversifolia (Wall. ex G. Don) Havil. (MD). Total phenolic, total condensed tannin, and total flavonoid contents were determined. Antioxidant activities were assessed using colorimetric assays. The results indicated that the leaf crude extract (LCE) had the highest total phenolic, total condensed tannin, and total flavonoid contents compared to the extracts from branches, stem barks, and fruits. The antioxidative capacity of LCE exhibited IC50 values of 459.19 ± 9.08 μg/ml for 2,2-diphenyl-1-picrylhydrazyl assay and 150.93 ± 7.59 μg/ml for lipid peroxidation assay, with an ferric ion reducing antioxidant power value of 279.88 ± 2.54 μM gallic acid equivalent/g extract. After fractionating the LCE through the Toyopearl® HW-40 column, the enriched polyphenolic fraction (Fr 5) was obtained. The chemical profiles of Fr 5 using high-performance thin-layer chromatography and liquid chromatography-electrospray ionization tandem mass spectrometry were constructed. All fractions were further evaluated for their protective effect on H2O2-induced oxidative stress in L6 myotubes cell line. The protective effect was found in cells treated with 25–100 μg/ml of Fr 5. The present study concluded that the enriched polyphenolic fraction of MD has antioxidative potential and reduces oxidative stress in L6 myotubes.
Keywords: Mitragyna diversifolia, antioxidative constituents, oxidative stress, L6 myotubes